(+)‐Isobicyclogermacrenal and spathulenol from Aristolochia yunnanensis alleviate cardiac fibrosis by inhibiting transforming growth factor β/small mother against decapentaplegic signaling pathway. (29th October 2018) - Lou, Lan‐Lan; Li, Wei; Zhou, Bin‐Hua; Chen, Lin; Weng, Han‐Zhuang; Zou, Yi‐Hong; Tang, Gui‐Hua; Bu, Xian‐Zhang; Yin, Sheng
Abstract : Cardiac fibrosis contributes to both systolic and diastolic dysfunction in many cardiac pathophysiologic conditions. Antifibrotic therapies are likely to be a crucial strategy in curbing many fibrosis‐related cardiac diseases. In our previous study, an ethyl acetate extract of a traditional Chinese medicine Aristolochia yunnanensis Franch. was found to have a therapeutic effect on myocardial fibrosis in vitro and in vivo. However, the exact chemicals and their mechanisms responsible for the activity of the crude extract have not been illustrated yet. In the current study, 10 sesquiterpenoids (1 –10 ) were isolated from the active extract, and their antifibrotic effects were systematically evaluated in transforming growth factor β 1 (TGFβ1)‐stimulated cardiac fibroblasts and NIH3T3 fibrosis models. (+)‐Isobicyclogermacrenal (1 ) and spathulenol (2 ) were identified as the main active components, being more potent than the well‐known natural antifibrotic agent oxymatrine. Compounds 1 and 2 could inhibit the TGFβ1‐induced cardiac fibroblasts proliferation and suppress the expression of the fibrosis biomarkers fibronectin and α‐smooth muscle actin via down‐regulation of their mRNA levels. The mechanism study revealed that 1 and 2 could inhibit the phosphorylation of TGFβ type I receptor, leading to the decrease of the phosphorylation levels of downstream Smad2/3, then consequently blocking the nuclear translocation of Smad2/3 in the TGFβ/Smad signaling pathway. These findings suggest that 1 and 2 may serve as promising natural leads for the development of anticardiac fibrosis drugs.